Public external debt bargaining - Cantamutto, Francisco J. (CLACSO, 2021)
This short policy brief results from a detailed analysis of the Argentinean case on external public debt during the last decade, with special attention on the huge 2005 swap. It is quite known for the Latin American experience that external debt has been a subordination mechanism, especially since the rise of the neoliberal stage. The systematic increase in debt services can make countries to become illiquid from time to time, forcing to go into default and renegotiate. This cycle of debt can boost economic activity when funds are coming, but produces severe crisis when they are no longer available. For Argentina, the economy opening process got its apotheosis during the Convertibilidad regime (1991-2001), which stated external debt payments as the main aim of public finance. This ended badly, with a default declaration on the hot December 2001